The Adam Berenz German Society and the Revitalization of the Ethnic Identity of Germans in Apatin - Aleksandar Krel (University of Belgrade, 2016)
At the time of the violent interethnic conflict in the former Yugoslavia, ethnic Germans in Serbia became publicly active for the first time after decades of "ethnic mimicry", founding ethnic German societies. It is through these societies that the process of revitalization and (re)construction of their ethnic and cultural identity has been taking place. There are about a dozen such societies active in Vojvodina today, one of them being the Adam Berenz German Society in the town of Apatin. The paper looks at the conceptualization and symbolization, analysis of ethnic strategies and presentation of modalities by means of which the Apatin association seeks to preserve and revive certain specific ethnic and cultural elements of the German ethnic community.